1997
DOI: 10.1183/09031936.97.10122725
|View full text |Cite
|
Sign up to set email alerts
|

Propeptide levels of type III and type I procollagen in the serum and bronchoalveolar lavage fluid of patients with pulmonary sarcoidosis

Abstract: No single test is available to reliably assess the activity or prognosis of pulmonary sarcoidosis. In this study, we have evaluated two procollagen markers, aminoterminal propeptide of type III procollagen (PIIINP) and carboxyterminal propeptide of type I procollagen (PICP) in serum and bronchoalveolar lavage fluid (BALF) and compared them to other disease markers of pulmonary sarcoidosis, such as serum level of angiotensin converting enzyme (S-ACE) or serum interleukin-2 receptor (S-IL-2R). Bronchoalveolar la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
3
19
0
1
Order By: Relevance
“…The radioimmunoassay used is very sensitive and precise for measurement of PIIINP in many human biological fluids including serum 9 and BALF. 22 The results of the present study indicated that the assay has good sensitivity, linearity, and reproducibility and acceptable accuracy for measurement of PIIINP in canine serum. Good cross-reactivity between human and canine PIIINP could be expected, given that collagen synthesis and metabolism are known to be well preserved throughout many mammalian species.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The radioimmunoassay used is very sensitive and precise for measurement of PIIINP in many human biological fluids including serum 9 and BALF. 22 The results of the present study indicated that the assay has good sensitivity, linearity, and reproducibility and acceptable accuracy for measurement of PIIINP in canine serum. Good cross-reactivity between human and canine PIIINP could be expected, given that collagen synthesis and metabolism are known to be well preserved throughout many mammalian species.…”
Section: Discussionmentioning
confidence: 74%
“…17 Serum and urinary PIIINP concentrations have been studied in humans with various renal diseases 18,19 as well as in patients after renal transplantation 20 and have been shown to correlate with the extent of organ fibrosis. In interstitial pulmonary conditions including pulmonary fibrosis, 5 acute respiratory distress syndrome 21 and sarcoidosis, 22 PIIINP concentrations in both serum and BALF are significantly increased, compared with values in samples from healthy individuals.…”
mentioning
confidence: 96%
“…In human medicine, numerous studies have been performed to assess the utility of PIIINP in the diagnostics of fibrosis. They revealed Serum concentrations of PIIINP...that this parameter may be useful in the diagnosis of idiopathic pulmonary fibrosis (Norris et al 2005), obstructive pulmonary disease (Harju et al 2010), sarcoidosis, (Lammi et al 1997) and the respiratory distress syndrome (Meduri et al 1998). In humans, PIIINP has also been found to be associated with the myocardial fraction of type III collagen and may be used as a marker of myocardial fibrosis (Izawa at al.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental lung granulomatous inflammation and in human lung sarcoidosis collagen type I can be detected predominantly at the periphery of granulomas, whereas procollagen type I appears to be present within the granulomas (Roman et al 1995). In studies from our laboratory, the concentrations of the aminoterminal propeptide of type III procollagen (PIIINP) and carboxyterminal propeptide of type I procollagen (PICP) were increased in the broncho-alveolar lavage fluid (BALF) and epithelial lining fluid (ELF) of patients with sarcoidosis (Lammi et al 1997) and idiopathic pulmonary fibrosis (i.e. UIP) (Lammi et al 1999).…”
Section: Introductionmentioning
confidence: 95%